HUBUNGAN PERSEPSI MASYARAKAT TENTANG FUNGSI RTH DENGAN PARTISIPASINYA DALAM PENYEDIAAN RTH DI KECAMATAN SERENGAN KOTA SURAKARTA TAHUN 2023 - Annisa Fajar Cahyani -; Sarwono; Setya Nugraha (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2025)
This research aims to (1) assess the level of community perception regarding the function of green open space, (2) measure community participation in providing green open space, and (3) analyze the relationship between community perception and participation. A quantitative research method was employed, using cluster random sampling in Serengan, Danukusuman, and Joyotakan villages. The study population consisted of families in Serengan District, with a sample of 100 respondents, determined using the Slovin formula. Data were collected through questionnaires and analyzed using descriptive statistics, simple regression, and Spearman rank correlation. Results indicate that 97% of respondents have a good perception of green open space, while community participation levels are low (61%), moderate (28%), and high (11%). The Spearman correlation test shows a very weak relationship (sig = 0.049, coefficient = 0.197). Simple regression (sig = 0.086) and chi-square tests (sig = 0.372, coefficient = 0.139) indicate that perception does not significantly influence participation. Other factors likely influence community participation in providing green open space.